A Phase 1 Study of 4 Live, Recombinant Human Cytomegalovirus Towne/Toledo Chimera Vaccines in Cytomegalovirus–Seronegative Men. (11th August 2016) - Adler, Stuart P.; Manganello, Anne-Marie; Lee, Ronzo; McVoy, Michael A.; Nixon, Daniel E.; Plotkin, Stanley; Mocarski, Edward; Cox, Josephine H.; Fast, Patricia E.; Nesterenko, Pavlo A.; Murray, Susan E.; Hill, Ann B.; et al.
Abstract: Background. Human cytomegalovirus (HCMV) infection causes disease in newborns and transplant recipients. A HCMV vaccine (Towne) protects transplant recipients. Methods. The genomes of Towne and the nonattenuated Toledo strain were recombined, yielding 4 Towne/Toledo chimera vaccines. Each of 36 HCMV-seronegative men received 1 subcutaneous dose of 10, 100, or 1000 plaque-forming units (PFU) in cohorts of 3. Safety and immunogenicity were evaluated over 12 weeks after immunization and for 52 weeks for those who seroconverted. Results. There were no serious local or systemic reactions. No subject had HCMV in urine or saliva. For chimera 3, none of 9 subjects seroconverted. For chimera 1, 1 of 9 seroconverted (the seroconverter received 100 PFU). For chimera 2, 3 subjects seroconverted (1 received 100 PFU, and 2 received 1000 PFU). For chimera 4, 7 subjects seroconverted (1 received 10 PFU, 3 received 100 PFU, and 3 received 1000 PFU). All 11 seroconverters developed low but detectable levels of neutralizing activity. CD4 + T-cell responses were detectable in 1 subject (who received 100 PFU of chimera 4). Seven subjects receiving chimera 2 or 4 had detectable CD8 + T-cell responses to IE1; 3 responded to 1–2 additional antigens. Conclusions. The Towne/Toledo chimera vaccine candidates were well tolerated and were not excreted. Additional human trials of chimeras 2 and 4 are appropriate. Clinical Trials Registration. NCT01195571.